Sedimen Prediktor dalam Analisa Debit Dominan - Endro P Wahono (UNIVERSITAS LAMPUNG, 2013)
One of the most important variables involved in river-channel formation is the channel-formingdischarge, which is well known as Dominant Discharge. Since discharge-sediment relation withinriver morphology process is quite dynamic and rather difficult to predict, it will be helpful to havea kind of representative discharge from analytical point of view.This paper discusses on how exponent (n) of sediment predictor affect dominant discharge deriva-tion. Two sediment predictors were used on this paper namely Engelund Hansen (EH) and Meyer-Peter-Muller (MPM). The result shows that, after deriving equations, the dominant discharge (Q d)could be explained as a maximum distribution value of piQ n/3 representing combination parameterof both probability and sediment predictor. Dominant discharge was then calculated based onthose two predictors and compared with average discharge, frequent discharge as well as bankfulldischarge. The result presents that analytical approach using EH predictor provides closer valueto the bankfull discharge.